Modern CMake for C++ effortlessly build cutting-edge C++ code and deliver high-quality solutions - Świdziński, Rafał (Packt Publishing Ltd., 2024)
Modern CMake for C++ isn't just another reference book, or a repackaging of the documentation, but a blueprint to bridging the gap between learning C++ and being able to use it in a professional setting. It's an end-to-end guide to the automation of complex tasks, including building, testing, and packaging software. This second edition is significantly rewritten, restructured and refreshed with latest additions to CMake, such as support of C++20 Modules. In this book, you'll not only learn how to use the CMake language in CMake projects but also discover how to make those projects maintainable, elegant, and clean. As you progress, you'll dive into the structure of source directories, building targets, and packages, all while learning how to compile and link executables and libraries. You'll also gain a deeper understanding of how those processes work and how to optimize builds in CMake for the best results. You'll discover how to use external dependencies in your project - third-party libraries, testing frameworks, program analysis tools, and documentation generators. Finally, you'll gain profi ciency in exporting, installing, and packaging for internal and external purposes. By the end of this book, you'll be able to use CMake confi dently at a professional level.
Includes bibliographical references and index
Keywords: C++ (Computer program language); Open source software; C++ (Langage de programmation); Logiciels libres